2022
DOI: 10.3928/1081597x-20211109-02
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity, Wavefront Aberrations, and Defocus Curves With an Enhanced Monofocal and a Monofocal Intraocular Lens: A Prospective, Randomized Study

Abstract: PURPOSE: To compare uniocular and binocular visual acuity, wavefront aberrations, and defocus curves using the TECNIS Eyhance (Johnson & Johnson) and RayOne (Rayner) intraocular lenses (IOLs). METHODS: In this prospective, randomized, comparative study, 50 patients (100 eyes) were randomized to receive the same IOL bilaterally ( ClinicalTrials.gov Identifier: NCT04175951). Follow-up visits were at 1 and 3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 22 publications
6
21
0
Order By: Relevance
“…Kang et al reported that Tecnis Eyhance can not only achieve superior intermediate vision and comparable visual performance at distance, but also generate low incidence of photic phenomena comparable to that of a Tecnis standard monofocal IOL [9]. Similar results were observed in other studies that compared the Tecnis Eyhance with Alcon and Rayner's standard monofocal IOLs [11,12].…”
Section: Introductionsupporting
confidence: 58%
“…Kang et al reported that Tecnis Eyhance can not only achieve superior intermediate vision and comparable visual performance at distance, but also generate low incidence of photic phenomena comparable to that of a Tecnis standard monofocal IOL [9]. Similar results were observed in other studies that compared the Tecnis Eyhance with Alcon and Rayner's standard monofocal IOLs [11,12].…”
Section: Introductionsupporting
confidence: 58%
“…Three clinical studies compared enhanced monofocals with EDoF lenses, [33][34][35] 14 compared the clinical results with a standard monofocal, [3,17,28,[36][37][38][39][40][41][42][43][44][45][46] and three case series without a comparison group were identified [16,47,48] Only one study included both monofocal and EDoF lenses in comparison to Tecnis Eyhance [49]. Supplemental file B contains all the data extracted from clinical studies.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Although four randomized clinical trials (RCT) were identified, [39,43,45,46] none accomplished all the requirements described by the ANSI for evaluating the EDOF criteria. Table 5 summarizes the criteria for classifying an intraocular lens as an EDOF according to the ANSI standard.…”
Section: Edof Criteriamentioning
confidence: 99%
“…On the other hand, Nanavaty et al found a clinically non-significant difference in total and internal SA with the TECNIS Eyhance IOL, indicating that the Eyhance IOL does not induce SA. 18 …”
Section: Discussionmentioning
confidence: 99%
“…De Luis Eguileor et al found a significant correlation between SA and intermediate VA; this endorses that with SA of intermediate values, the Eyhance IOL offers better intermediate VA. 9 On the other hand, Nanavaty et al found a clinically non-significant difference in total and internal SA with the TECNIS Eyhance IOL, indicating that the Eyhance IOL does not induce SA. 18 The Eyhance can be offered to patients undergoing routine cataract surgery. It is a great choice when premium IOLs are not desired.…”
mentioning
confidence: 99%